Application Of Artificial Intelligence In The Future Practice Of Advocates - zulmawan, wawan (Jurnal Rechts Vinding: Media Pembinaan Hukum Nasional, 2024)
Artificial Intelligence (AI) technology provides benefits for professional work, including for advocates. Indonesia government has prepared National Strategy Framework for Artificial Intelligence. By using empirical normative legal research methods from primary and secondary sources, in form of books, journals and statutory regulations, it can be seen that Circular Letter of the Minister of Communication and Informatics number 9 of 2023 concerning Ethics of Artificial Intelligence can be used as a legal basis by advocates to exercise their rights to obtain data. Research show that there are several AI technologies can be used in the future by advocates, such as SBVR, NER or ChatBot Platform. Research also show Artificial Intelligence regulations still require stronger regulations, and Indonesia government also needs to form a Committee related to Artificial Intelligence to monitor and provide sanctions related to ethical violations in use of artificial intelligence.